Modest Wear dengan Unsur Tabir Pelaminan Melayu Siak - Audyra Nasya; Mega Kencana; Desi Trisnawati; Fendi Nofrian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This work, titled "Modest Wear with Elements of the Siak Malay Wedding Dais Canopy," draws inspiration from the decorative canopy panels—characterized by tongue-like shapes—found on the ceilings of Siak Malay wedding daises. These forms have been adapted into modest wear designs across three categories: ready-to-wear, ready-to-wear deluxe, and haute couture. The creation process incorporates Songket Siak—a traditional woven fabric—featuring the bunga tanjung (tanjung flower) motif, a signature design from Riau. The color palette reflects the traditional Siak Malay wedding dais—red, yellow, and green—while details such as tekat embroidery featuring the pucuk pakis (fern shoot) motif—another Riau signature—are applied to the garments. Materials utilized include bridal satin, Kawasaki silk, pleated satin, and Songket Siak. The creative process involved observation, interviews, and reference gathering related to the concept, alongside a literature review concerning modest fashion and Siak Malay wedding daises. The designs incorporate 2025 trend forecasts for contemporary modest fashion, emphasizing simple, minimalist, and loose-fitting silhouettes. The resulting collection comprises three tiers: ready-to-wear (Suji Seloka), ready-to-wear deluxe (Suji Danendra), and haute couture (Suji Singgasana). These garments were showcased at the "Malenggang #4" event—themed "Fashion Fusion"—held at the Hoeridjah Adam Performance Hall gallery at the Indonesian Institute of the Arts (ISI) Padangpanjang on June 2, 2026.